2007
DOI: 10.1021/ma061734k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Order Formation in Block Copolymer Thin Films Using Resonant Soft X-ray Scattering

Abstract: The lateral order of poly(styrene-block-isoprene) copolymer (PS-b-PI) thin films is characterized by the emerging technique of resonant soft X-ray scattering (RSOXS) at the carbon K edge and compared to ordering in bulk samples of the same materials measured using hard Xray small-angle scattering. We show using theory and experiment that the loss of scattering intensity expected with a decrease in sample volume can be overcome by tuning X-rays to the π* resonance of PS or PI. Using RSOXS, we study the micropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 39 publications
0
95
0
Order By: Relevance
“…Emerging new methods include resonant X-ray scattering [109], for enhanced contrast, critical-dimension SAXS, giving access to a 3D reconstruction [110] of in-depth structural features in the films, and scattering infrared near-field microscopy [111], for nanoscale chemical analysis at surfaces.…”
Section: Experimental Techniques For the Structural Studies Of The Namentioning
confidence: 99%
“…Emerging new methods include resonant X-ray scattering [109], for enhanced contrast, critical-dimension SAXS, giving access to a 3D reconstruction [110] of in-depth structural features in the films, and scattering infrared near-field microscopy [111], for nanoscale chemical analysis at surfaces.…”
Section: Experimental Techniques For the Structural Studies Of The Namentioning
confidence: 99%
“…This dependence has two major consequences: i) "bond-specific" or functional group specific scattering can be achieved in R-SoXS by judicious choice of photon energy [6][7][8], in a manner analogous to NEXAFS microscopy of polymers [ 22,23], ii) in addition, Δδ 2 +Δβ 2 overcomes or at least neutralizes the E 4 factor that would favor use of higher energy photons and orders of magnitude larger scattering intensity can be achieved near the carbon edge relative to photons with E ∼10 keV as used in conventional SAXS [7,11]. This affords the opportunity to get useable scattering intensities in transmission even from rather thin films only 20-200 nm in thickness [7][8][9]24]. More recently, it has been pointed out and demonstrated that R-SoXS furthermore has unique contrast to bond orientation if polarized light and polarization control of the incident photons are available [24].…”
Section: Contrast Mechanism With Soft X-raysmentioning
confidence: 99%
“…Applications of R-SoXS to systems other than organic devices include the characterization of block copolymers (BCPs) [9,55,56]. We will exemplify the benefit of using energy dependent selective contrast as provided by R-SoXS by reviewing a recent study of a block copolymer with a complex and unique morphology [56].…”
Section: In-plane Block Copolymer Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft X-ray resonant reflectivity/scattering studies are finding application in soft mater polymer films [37][38][39][40][41][42][43][44][45][46], and biological samples [47]. However the utility of soft Xray resonant for studies of atomic composition at buried interface, depth profiling of variation in atomic density, native oxide and films of nearly equal electron density studies of hard condensed matter thin films/multilayers is not significantly exploited.…”
Section: Introductionmentioning
confidence: 99%